PENGARUH JENIS AGREGAT RINGAN BUATAN TERHADAP KUAT TEKAN BETON RINGAN = EFFECT OF ARTIFICIAL LIGHTWEIGHT AGGREGATE TYPE FOR COMPRESSIVE STRENGTH OF LIGHTWEIGHT CONCRETE - sulistyowati, Nurul aini; suripto, Deden (Jurnal Material Komponen dan Konstruksi, 2013)
The aim of the research was to know the mechanical and physical properties of lightweight aggregate and compressive strength of concrete with lightweight aggregate. The raw materials for manufacturing lightweight aggregate include the mix composition of shale + sawdust, shale + rice husk, shale + rice husk ash, and shale. Th structural lightweight concrete was designed to have a compressive strength of 25 MPa. The specimen was cylindrical of 10 diameter and 20 cm high. The compressive strength of concrete tested at ages of 14 days, 21 days, and 28 days. Specific gravity of lightweight aggregate was less than 1.5, the best water absorption was of the lightweight aggregate shale and the best hardness that of the lightweight aggregate shale+ rice husk ash. The compressive strength of concrete with lightweight aggregate shale + sawdust 265.04 kg/cm2 and shale + rice husk ash 264.73 kg/cm2, all of which were higher than compressive strength. The compressive strength of concrete with lightweight aggregate shale + rice was husk 234.82 kg/cm2 and that of the shale was 212.23 kg/cm2 , which were lower than the designed compressive strength.Keywords : artificial lightweight aggregate, lightweight concrete, shale, sawdust, rice husk, rice husk ashÃ‚Â AbstrakPenelitian bertujuan untuk mengetahui sifat fisis dan mekanis agregat ringan serta kuat tekan beton yang menggunakan agregat ringan. Pembuatan agregat ringan menggunakan komposisi campuran shale + serbuk gergaji kayu, shale + abu sekam padi, shale + sekam padi, serta shale. Pembuatan beton ringan struktural menggunakan rancangan campuran dengan kuat tekan rencana sebesar 25 MPa. Benda uji berbentuk silinder dengan diameter 10 cm dan tinggi 20 cm. Pengujian kuat tekan beton dilakukan pada umur 14 hari, 21hari dan 28 hari. Berat jenis agregat ringan kurang dari 1,5 dengan penyerapan air terbaik pada agregat ringan shale dan kekerasan terbaik pada agregat ringan shale + abu sekam padi. Kuat tekan beton agregat ringan shale + serbuk gergaji sebesar 265,04 kg/cm2 dan agregat ringan shale + abu sekam padi 264,73 kg/cm2 lebih tinggi dari kuat tekan rencana. Kuat tekan beton agregat ringan shale + sekam padi sebesar 234,82 kg/cm2 dan agregat ringan shale sebesar 212,23 kg/cm2 lebih rendah dari kuat tekan rencana.Kata kunci : agregat ringan buatan,beton ringan, shale, serbuk gergaji kayu, sekam padi, abu sekam padi